Spatio-temporal population and reproductive responses in Perinereis gualpensis (Polychaeta: Nereididae) from estuaries under different anthropogenic influences - Diaz Jaramillo, Mauricio Javier (2015)
Reproductive and population-level responses are ecologically relevant diagnostic tools for revealing the cost of long-term tolerance to contaminants. Spatial density distribution, seasonal density, biomass, size frequency histograms and oocytes stages in Perinereis gualpensis (Polychaeta: Nereididae) from a highly anthropogenically impacted estuary (Lenga, south-central Chile) were compared with low-polluted estuaries (Tubul and Raqui). Spatial distribution showed that the highest P. gualpensis abundances occur in the central (middle) estuarine area, establishing them as suitable zones for comparisons of estuaries. Middle areas also showed differences among estuaries in terms of population and reproductive responses. Mature stage oocytes and juvenile recruitment limited to certain seasons and low adult survival led to significant low densities and biomasses in Lenga individuals (p <.05). Conversely, high densities and biomass, continuous recruitment and mature oocyte occurrence were observed in Tubul–Raqui estuaries. These results reflected population and reproductive differences among high- and low-polluted estuaries, suggesting that chronic pollution status in Lenga estuary is a factor to be considered when evaluating these responses.